Factors Affecting Voluntary Turnover Intent of Fast Food Industry in Klang Valley, Malaysia - Thong, Chun Fat (2013)
Turnover intent of employee has become one of the essential topics in job market, organizations or industries. This topic has made by many researchers before, there are so many factors, organizational factors, and environmental factors will focus on this research because most of the turnover intent started with job satisfaction, promotion of the organization, and also environmental issues. In addition, studies on job related factors, organizational factors and environmental factors toward employees’ turnover intention specifically in the fast food industry of Malaysia are limited. The objective of this research is to investigate the influence of job related factors, organizational factors and environmental factors towards turnover intention in the fast food industry. The total respondents are 151 from middle level until the lower level employees in the fast food industry. Sampling location is Klang Valley, Malaysia. By using the factor analysis and multiple regressions; it found that job related factors, organizational factors and environment factors give an impact on turnover intent in the fast food industry.